2023
DOI: 10.1039/d3cp02755d
|View full text |Cite
|
Sign up to set email alerts
|

Strong anisotropy of Sc2X2Se2 (X = Cl, Br, I) monolayers contributes to high thermoelectric performance

Xiefei Song,
Xihao Chen,
Guangzhao Wang
et al.

Abstract: As a novel type of anisotropic two-dimensional materials, the thermoelectric (TE) properties of FeOCl-type monolayers have received extensive attention, such as Al2X2Se2 (X = Cl, Br, I), Sc2I2S2, and Ir2Cl2O2....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…are potential candidates for TE applications owing to their considerably high electronic fitness function values . Several subsequent studies have demonstrated that Al 2 X 2 Se 2 (X = Cl, Br, and I), Sc 2 X 2 Se 2 (X = Cl, Br, and I), and TiNX (X = F, Cl, and Br) monolayers are excellent TE materials. Moreover, the ScSI monolayer has been successfully exfoliated for the first time and is predicted to be an excellent n-type TE material with anisotropic properties based on third-order force constants. , Although ScSX (X = Cl, Br, and I) monolayers have been extensively researched and show promise for nanotechnology applications, their TE properties have not been well established.…”
Section: Introductionmentioning
confidence: 99%
“…are potential candidates for TE applications owing to their considerably high electronic fitness function values . Several subsequent studies have demonstrated that Al 2 X 2 Se 2 (X = Cl, Br, and I), Sc 2 X 2 Se 2 (X = Cl, Br, and I), and TiNX (X = F, Cl, and Br) monolayers are excellent TE materials. Moreover, the ScSI monolayer has been successfully exfoliated for the first time and is predicted to be an excellent n-type TE material with anisotropic properties based on third-order force constants. , Although ScSX (X = Cl, Br, and I) monolayers have been extensively researched and show promise for nanotechnology applications, their TE properties have not been well established.…”
Section: Introductionmentioning
confidence: 99%
“…The monolayer FeOCl-type materials have attracted great attention because of their unique anisotropic structures. For example, ABX (AIn, Al, Sc, Ti, Zr, and Hf; BS, Se, and N; XF, Cl, Br, and I) shows excellent thermoelectric and photoelectric properties. The GaSCl crystal was first reported to have been synthesized in 1963 . And 2D GaSCl has been predicted to have strong p-type anisotropy and a small hole-effective mass. , This unique anisotropic structure not only affects the thermoelectric and photoelectric properties of materials but also has a positive effect on their electronic transport properties .…”
Section: Introductionmentioning
confidence: 99%